The feasibility of assessing prognosis over 3 years in persons with a previous stroke/transient ischemic attack in general practice - Eimear Ryan; Harmeet Gill; Róisín Doogue; David McCann; Andrew W. Murphy; Peter Hayes (Pilot and Feasibility Studies)
Abstract Background Stroke has devastating consequences for survivors. Hypertension is the most important modifiable risk factor, and its management largely takes place in primary care. However, most stroke-based research does not occur in this setting. Ongoing hypertension and a risk of further stroke are a major concern for both patients and their general practitioners. We aim to assess whether it is feasible to assess prognosis in persons, with a previous stroke or transient ischemic attack (TIA), in general practice, and whether a well-powered observational study is possible. Methods We performed a search of the electronic health record of individuals previously identified as having had a stroke or TIA, to assess prognosis over 3 years. Feasibility was assessed by meeting five criteria: (1) all general practices approached participated, (2) greater than 90% of patient records were accessible, (3) all study outcomes were available to review, (4) that collection data was less than 15 min per patient, and (5) a power calculation for a planned observational study could take place. Results All six general practices approached participated freely, and 193/196 patients’ files were reidentified (98.5%). Twenty-eight cardiovascular events were recorded—most commonly a repeat TIA or ischemic stroke. Data collection took on average 5.5 min per file, and a power calculation for a planned observational study was completed. Conclusion This study demonstrates that the proposed methodology for a full cohort study within general practice of patients post-stroke/TIA is both acceptable to practices and feasible. An adequately powered, “time-to-event” study is possible.